Composição e diversidade filogenética da chuva de sementes: efeitos de manejos agropastoris e da sazonalidade climática em áreas de caatinga - Fernandes, Mychelle de Sousa (2024)
Forests worldwide have been impacted and modified by anthropogenic activities. In the Brazilian Seasonally Dry Tropical Forest, the Caatinga, a very low percentage of its native vegetation is preserved mainly due to agropastoral practices, which involve cutting and burning of the original vegetation, wood extraction, and implementation of pastures for livestock purposes. In addition to this context, the Caatinga is characterized by climatic seasonality, with irregular precipitation events and low annual averages. Environmental modifications through vegetation management and climatic seasonality have influenced the trends of different life history processes of species, especially plants. To understand the structure and organization of plant communities, it is essential to consider the diversity, phylogeny, and evolution of components, as well as key ecological processes such as seed dispersal. Therefore, the aim of this research was to investigate the influence of agropastoral management and climatic seasonality on the composition and phylogenetic diversity of seed rain in a Caatinga area. For this purpose, an experiment with collectors was implemented to capture seed rain in the dry and rainy seasons in different agropastoral management areas. Fruits and seeds were separated and taxonomically identified to provide important data on the composition and phylogenetic diversity of dispersed species. A phylogeny was constructed from the taxon list using the U.PhyloMaker package, which served as the basis for calculating Phylogenetic Diversity (PD), mean distances between taxa and nearest relatives (MPD and MNTD), as well as standardized measures of relatedness (NRI and NTI). Diaspores/seeds from 42 species belonging to 26 genera and 13 botanical families were found. Among the occurring species, 31 were recorded in the Preserved Caatinga area, 21 in the Thinned Caatinga, and 18 in the Caatinga with Pasture. The families with the highest species richness were Fabaceae, Poaceae, Convolvulaceae, and Asteraceae, which reinforces occurrence and richness patterns found in other Caatinga studies. There was a significant interaction between management and seasonality in phylogenetic diversity, with emphasis on thinning management and the dry season, whose interaction resulted in a comparative reduction in phylogenetic diversity, indicating that the effects of the dry season on PD can be modulated by the type of management implemented. The opposite occurs when PD is evaluated during the rainy season in the preserved area, with an increase in diversity. No significant differences were observed between management areas and seasons in the NRI, indicating that such variables did not affect the degree of relative kinship between species. The NTI demonstrated greater phylogenetic proximity between species in the thinned area during the rainy season compared to the pasture area in the dry season. These findings show that land management practices and seasonal conditions are closely linked, playing fundamental roles in modeling the phylogenetic diversity of plants, and may, on the other hand, have a moderate impact on the metrics of phylogenetic structure.